Senior High School Learning Motivation on Physics Subject - Sari, Nurmalita; Sunarno, Widha; Sarwanto, Sarwanto (Universitas Negeri Malang, 2017)
Abstract: Learning motivation is students’ willingness to study that comes from within. The objective of this research was to find out Senior High School students’ learning motivation level for physics subject. The subjects of this research were 60 students from Science Class of Senior High School 5 Surakarta who were randomly selected. A questionnaire was used as an instrument to measure students’ learning motivation. The result showed that students’ learning motivation in physics subject was categorized as medium level with an average score of 20.42. The percentage for each aspect was as follows: attention (24.33%), relevance (24.98%), confidence (24.33%), and satisfaction (25.71%).Keywords: ARCS, learning, motivation, physicsAbstrak: Motivasi belajar merupakan daya dorong dari dalam diri siswa untuk belajar. Penelitian ini bertujuan untuk mengetahui tingkat motivasi belajar siswa Sekolah Menengah Atas untuk mata pelajaran fisika. Penelitian dilaksanakan di SMA Negeri 5 Surakarta dengan subyek penelitian sebanyak 60 siswa jurusan MIPA yang dipilih secara random. Instrumen penelitian yang digunakan untuk mengukur motivasi belajar adalah angket. Angket motivasi dikembangkan berdasarkan aspek ARCS (Attention, Relevance, Confidence, Satisfaction). Berdasarkan hasil penelitian, tingkat motivasi belajar siswa untuk mata pelajaran fisika termasuk kategori sedang dengan rata-rata 20,42. Persentase dari masing-masing aspek motivasi belajar adalah Attention/perhatian (24,33%), Relevance/relevansi (24,98%), Confidence/percaya diri (24,33%) dan Satisfaction/kepuasan (25,71%).Kata kunci: ARCS, belajar, fisika, motivasi